CITRAAN DALAM KUMPULAN SAJAK TEBARAN MEGA KARYA SUTAN TAKDIR ALISJAHBANA - Lia Dimai Fitri; Bakhtaruddin Nasution; Zulfadhli Zulfadhli (Faculty of Languages and Arts, Universitas Negeri Padang, 2014)
The purpose of this article is (a) to describe the types of images contained in a collection of poems Tebaran Mega created by Sutan Takdir Alisjahbana, (b) to describe the functions contained in a collection of poems Tebaran Mega by Sutan Takdir Alisjahbana. The data of this study is a collection of images in poems Tebaran Mega by Sutan Takdir Alisjahbana. The technique of analyzing data using detailed description techniques . The research findings in this study is the first, of the 6 types of images were examined, found 5 images in a collection of poems Tebaran Mega which is as follows: visual imagery found in 28 poems, auditory imagery found in 21 poems, olfactory imagery found in one poems, imagery feelings found as many as 11 poems, images grope found as many as 11 poems, and motion imagery found in 24 poems. Second, there are three functions in the collection of poems Tebaran Mega by Sutan Takdir Alisjahbana which is as follows: the function of imagination as much as 10 poems, aesthetic function was found in 7 poems, and suggestive function found in 4 poems.